Revitalisasi filsafat skolastik dalam pendidikan agama Katolik: upaya kontekstualisasi tradisi Gereja di Keuskupan Agung Kupang - Patricius Neonnub (STIPAS Keuskupan Agung Kupang, 2025)
The crisis of relativism, post-truth, and the weak rationality of faith among the young generation of Catholics in Indonesia, especially in the Kupang Archdiocese, demands a new approach in Catholic religious education. This article offers a revitalization of scholastic philosophy, particularly the dialectical method of Saint Thomas Aquinas, as a framework for culturally and spiritually relevant, contextually grounded catechesis. This study employs a qualitative literature review approach, drawing on scholastic traditions, Church documents, and national Catholic religious education policies. The results of the study show that the scholastic method—with a quaestio–obiectio–responsio–ad obiecta pattern—can be inculcated in religious learning in formal schools through critical dialogue, faith reflection, and the use of local cultural symbols. The main contribution of this article is the offer of a scholastic–contextual integrative model that unites the intellectual tradition of the Church with contemporary pedagogical needs. The implications of this research include the need to train PAK teachers as reflective catechists, so that the scholastic tradition is not only a historical heritage, but also a living tradition that forms a reasoned faith.